Determining quantum efficiency of the pH-sensitive dye in mesoporous thin films using a metal sphere - Özelci, Ersan; Rühle, Bastian; Weigert, Florian; Lubotzky, Boaz; Kewes, Günter; Resch-Genger, Ute; Benson, Oliver (Frontiers in Optics - Proceedings Frontiers in Optics + Laser Science APS/DLS, 2019)
We show that Drexhage-type experiment where the silver-coated millimeter-sized sphere is used to measure the local quantum efficiency of pH-dependent fluorescein isothiocyanate bound to a mesoporous silica thin film.
CRIS-Team Scopus Importer:2023-04-20